2019
DOI: 10.1080/13588265.2019.1682351
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cell wall material strain and strain-rate hardening behaviour on the dynamic crush response of an aluminium multi-layered corrugated core

Abstract: The effect of the parameters of the Johnson and Cook material model on the direct impact crushing behaviour of a layered 1050 H14 aluminium corrugated structure was investigated numerically in LS-DYNA at quasi-static (0.0048 m s À1 ) and dynamic (20, 60, 150 and 250 m s À1 ) velocities. Numerical and experimental direct impact tests were performed by lunching a striker bar onto corrugated samples attached to the end of the incident bar of a Split Hopkinson Pressure Bar set-up. The numerical impact-end stress-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Shock enhancement is often used to explain the strength increase of the material at high strain rates [31,32]. The r-p-p-l model predicts merely the shock stresses [12]. To this end, the variation of stress over time is calculated using the following procedure: The impact of a uniform cellular material on a rigid wall with an initial velocity of v o induces two distinct deformation regions: a crushed (densified) region with a stress of σ * (initial crushing stress) and the elastically deformed region as seen in Fig.…”
Section: Rigid-perfectly-plastic-locking (R-p-p-l) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Shock enhancement is often used to explain the strength increase of the material at high strain rates [31,32]. The r-p-p-l model predicts merely the shock stresses [12]. To this end, the variation of stress over time is calculated using the following procedure: The impact of a uniform cellular material on a rigid wall with an initial velocity of v o induces two distinct deformation regions: a crushed (densified) region with a stress of σ * (initial crushing stress) and the elastically deformed region as seen in Fig.…”
Section: Rigid-perfectly-plastic-locking (R-p-p-l) Modelmentioning
confidence: 99%
“…Their numerical study showed that above 100 s − 1 , the effect of strain rate sensitivity of matrix outweighs the effect of micro-inertia. Güden and Canbaz [12] investigated the strain rate hardening of a layered 1050 H14 aluminium corrugated structure both experimentally and numerically through a direct impact test method. It was shown that the initial peak stress of a low strain rate hardening aluminium alloy was mostly influenced by micro-inertia.…”
Section: Introductionmentioning
confidence: 99%